Impact of Unwanted Pregnancy on Adolescents - Nur Fitri Ayu Pertiwi; Liza Laela Abida (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Unwanted pregnancy in adolescents is a global problem that needs attention. Undesirable impact on all adolescents for the entire life of adolescents. Physical, economic, and social impacts will affect the future of adolescents. The purpose of the study was to determine the unwanted impact on adolescents. The research method is a scoping review using a search engine in the PubMed and Science Direct databases from January 2013 to December 2021. Based on the results of the scoping review, the theme was found: "the impact of unwanted pregnancy on adolescents". Keywords: Unwanted Teen Pregnancy, Physical Impact, Economic Impact, Social Impact